LABOR. A Statue Group in the Monument to Alexander II in Helsinki - Eeva Maija Viljo (ICO Iconographisk Post, 2021)
The statue group LABOR that forms part of the monument to Alexander II of Russia, Grand Duke of Finland, in Senate Square in Helsinki (inaugurated 1894) is discussed in the context of labour movement iconography by Fred Andersson in an article in Iconographisk Post 3/4 2020. The proposals of the sculptor Walter Runeberg (1838–1920) for LABOR paired Agriculture, a mature woman harvester, and a youthful Industry with tools and machinery. The latter figure was rejected and replaced by a farmer with an axe to indicate his role as a rural worker felling timber, the raw material of the forestry industries. The harvesting woman and the farmer-logger form a couple, and the arrangement of Agriculture’s garments intimates that she might be pregnant. The surmise is affirmed in sculptor Emil Wikström’s (1864–1942) tympanum frieze on the façade of the House of the Estates (erected in 1902), in which he has placed the farming couple of LABOR, the man turning earth with a spade and his seated wife teaching their small son to read. The tableau can be read as a comment on the contemporary drive for compulsory elementary education in Finland. LABOR and the tympanum frieze, which has as its central figure Alexander I in 1809 giving his ruler’s affirmation to the Estates assembled to swear their pledge of loyalty to the new ruler, are to be understood in the context of Finnish nationalist politics rather than the imagery of the international workers’ movement. The figures of LABOR are, however, indebted to the art of French Realism, which favoured agricultural workers as motifs around the middle of the 19th century and which was linked to socialist movements.